MENJEMBATANI OTAK DAN BAHASA: EKSPLORASI PERSEPSI MAHASISWA PASCASARJANA TENTANG NEUROEDUKASI DALAM PENGAJARAN BAHASA INGGRIS - Indahsari, Dahlia; Nugroho, Him’mawan Adi; Munir, Ahmad (STKIP Siliwangi, 2025)
This study aims to explore postgraduate students' perceptions of the importance of Neuroeducation in English Language Teaching (ELT) and their awareness of its application. A mixed-methods approach was employed in this study. The study involved 30 postgraduate students from Master of Education programs at various universities. Questionnaires were used to collect quantitative data, while open-ended interviews were conducted to gather qualitative data. The data were analyzed using descriptive statistics for the quantitative data and thematic analysis for the qualitative data. The findings reveal that postgraduate students perceive understanding brain function as crucial in ELT. Regarding the awareness of Neuroeducation, participants highlighted the significance of accessible neuroscience resources, with the highest mean score (M = 4.87) for the need to make neuroscience information easily available to educators. The study concludes that postgraduate students recognize the importance of Neuroeducation in creating personalized and inclusive learning environments, though challenges remain, such as the need for formal training. Thus, Neuroeducation is considered an interdisciplinary field that can bring insights into how the brain learns the knowlegde into more effective and inclusive teaching stratgies, particularly in English language teaching.